Gestión del riesgo de desastres para la reducción de la vulnerabilidad en la I.E José Faustino Sánchez Carrión, Pacayzapa - Oblitas Quiroz, Víctor Hugo (2011)
Risk management is a complex social process designed to reduce, prevent and control the risks associated with the hazards or minimize their effects, including intervention measures and ways of intervention that tend to reduce, mitigate, prevent and respond to disasters. In our country the geotectonic processes have determínate unique geomorphology shapes, whose greatest expression constitutes the Andes, in addition to that, the Amazon basin and the presence of the Peruvian current, they cause we are exposed to several hazards, such as earthquakes, landslides, mudslides and erosion, as well as climatic variations in certain regions. The risks from these hazards adversely affect the productive capital of the country as agricultural, industrial, economic infrastructure such as bridges, roads, energy, and social infrastructure such as housing, basic health services, education and clean water. This has a negative impact on the living conditions ofthe population, not only in the short term but in the medium and long term, in terms of economic growth. In the San Martín region, the climate conditions are known for its heavy rainfall, the loss of forest cover and accelerated erosion, make that today we face constant risk conditions, particularly as regards the dangers of flooding and landslides. Educational Institution José Faustino Sánchez Carrión, while its institutional life has faced periodically overflowing of the Cangrejillo creek, on whose banks it's located their local school. The obvious solution to the problem is the relocation, which involves replacing 12 classrooms (04 of which have been built recently), a computer lab, administrative offices, complementary and necessary service to serve 354 students currently attending the institution, ensuring that the distance to the sources of danger put to guard the institution and its educational community. The resources required for the implementation of these actions definitely cannot be immediately attended, for that reason it been develop a pre investment study at profile level to address inadequate access to educational services in the institution, study in which we consider the relocation of the infrastructure, however, there were problems during the execution of the first stage of the project, have made to invest foreign resources in the current property.